Strengths and Challenges of Arts-Based Programming for Individuals With Alzheimer’s and Related Dementias (LEARNing Landscapes, 2017)
Through the perspectives of a museum educator, an art educator, and an educational researcher, this article explores the evolution of shared definitions of “well-being” in the development of a museum- and arts-based program for adults with Alzheimer’s disease and related dementias (ADRD). By piecing together the authors’ first-person reflections on pivotal program design moments with images, participant quotes and reflections, and emerging quantitative data, this bricolage inquiry provides insight into the complex and sometimes competing conceptions of wellness and learning that arise in designing programming with and for this population and their caregivers.
Keywords: well-being; shared meaning; musuem; arts-based; Alzheimer’s disease; learning